Politik penegakan hak asasi manusia pada masa transisi d Indonesia - Halili, Halili (Universitas Negeri Yogyakarta, 2016)
This article was aimed at (1) discovering and constructing the political dynamics in formulating the Law of the Court of Human Rights; (2) analyzing its implication on the future of politic of Human Rights in Indonesia. This essay was a result of content analysis research with qualitative-comparative approach. The finding showed that (1) substantively, the formulation of Law No. 26 Year 2000 on Human Rights Court has fundamental weaknesses such as a partial adaptation of The Roma Statute, the course of human rights court was constructed weak by stating its authority only on investigation, whereas attorney General's Office authority on investigation lacks of detail prescription, deleting the responsibility of command such as those on the Rome Statute, etc. A lot of lacks indicate that the law was only an instrument of transitional authority. The